Estudo das práticas de gestão dos empreendimentos econômicos solidários no âmbito regional: análise multicaso nas cooperativas incubadas de reciclagem Coopercicla e Coorepa - Chalub, Wladislau Guimarães Silva (2018)
The capitalist system has transformed the social relations of labor, changed the traditional forms of production and provision of services. Nevertheless, brought huge differences between developed countries and those in developing process, between rich and poor, owners of the means of production and holders of the labor force, leading to geographical inequalities, social exclusion and increase in unemployment. It is in this context that the "Solidarity Economy" appears as one of the alternatives to the traditional economic model, becoming a way of combating unemployment and sharing the idea of support, protection, assistance, solidarity, cooperation and self - help for workers in a situation of vulnerability or without formal employment. Thus, the solidarity economy is conceived as economic activities organized by workers who practice the self - management, in the way as the cooperatives connected to this kind of economy promote the development among the members, what may be a competitive strategy in the search for advantages and sustainability. This way, this research investigated the practices of shared management in connection to the principles of the solidarity economy in regional recycling cooperatives, Cooperative Recycles Paranaíba (COOREPA /MS) and Ituiutaba Recycling Cooperative (COOPERACICLA/MG), considered in this study as units of analyses investigated. As for the approach, this investigation is classified as qualitative research, having as purpose the descriptive form and as technical procedure was used the case study. The collection was by means of analyses of official documents held by the cooperatives investigated and reports published by bodies such as IBGE, OCEMG,OCB/MS, Organization of the cooperatives of Brazil (OCB) among others related to the topic addressed . The relevant results found show that the principles of the solidarity economy are tied to the cooperatives studied. However, it has identified a significant lack of knowledge on the part of the majority of the cooperative ones, on regarding their understanding about self- management , shared democratic management and the rights and duties of their associated / cooperative status. It is concluded that the recycling cooperatives studied were part of the incubation process via federal universities (UFU and UFMS), which in the first instance strengthened the cooperative's work process, but are currently developing their commercial activities with relative autonomy and distant from the universities that incubated them within the logic of collective economic solidarity enterprising.